Euro Area Policies : 2007 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Member Countries. (IMF Staff Country Reports; Country Report ;, 2007)
The Euro Area Policies' 2007 Article IV Consultation reports that the economy is poised for a sustained upswing because of cyclical considerations and policies, which have had a forward-looking cast. The area's external position and the real effective exchange rate of the euro are within range of medium-term equilibrium. Stabilizing inflation below 2 percent might well require a further gradual tightening of monetary policy. Increased contestability and integration in the financial sector is also key to improving performance.